Role of productive capacities on agricultural productivity in BRI countries - Mustafa, Ghulam; Madni, Ghulam Rasool; Naeem, Muhammad; Alotaibi, Bader Alhafi; Nayak, Roshan K (Frontiers in Sustainable Food Systems, 2025)
Agricultural productivity is a cornerstone of food security, poverty alleviation, and sustainable development. While traditional determinants such as land, labor, credit, and water have been widely studied, the broader role of national productive capacities remains underexplored, particularly in the context of the Belt and Road Initiative (BRI). This study investigates the impact of productive capacities on agricultural productivity in 42 BRI countries from 2000 to 2024, using the Productive Capacities Index (PCI) alongside conventional inputs. The study employed the system GMM and 2SLS econometric techniques and then employed other econometric techniques such as Driscoll-Kraay, Feasible Generalized Least Squares (FGLS), and Panel-Corrected Standard Errors (PCSE) to check the robustness of the results. It is found that higher productive capacities significantly enhance agricultural productivity, while access to credit, land expansion, and water availability also play critical roles. Labor contributions, however, show mixed effects, suggesting inefficiencies in labor-intensive farming systems. By integrating PCI, this study provides a novel, cross-sectoral perspective on agricultural development. The findings underscore the importance of strengthening infrastructure, technology, institutions, and human capital within the BRI framework to foster sustainable agricultural growth and regional food security.